Searching for Differences in Race: Is There Evidence for Preferential Detection of Other-Race Faces? - Lipp, Ottmar; Terry, D.; Smith, J.; Tellegen, C.; Kuebbeler, J.; Newey, M. (American Psychological Association, 2009)
Previous research has suggested that like animal and social fear-relevant stimuli, other-race faces (African American) are detected preferentially in visual search. Three experiments using Chinese or Indonesian faces as other-race faces yielded the opposite pattern of results: faster detection of same-race faces among other-race faces. This apparently inconsistent pattern of results was resolved by showing that Asian and African American faces are detected preferentially in tasks that have small stimulus sets and employ fixed target searches. Asian and African American other-race faces are found slower among Caucasian face backgrounds if larger stimulus sets are used in tasks with a variable mapping of stimulus to background or target. Thus, preferential detection of other-race faces was not found under task conditions in which preferential detection of animal and social fear-relevant stimuli is evident. Although consistent with the view that same-race faces are processed in more detail than other-race faces, the current findings suggest that other-race faces do not draw attention preferentially. © 2009 American Psychological Association.